2006
DOI: 10.1073/pnas.0604708103
|View full text |Cite
|
Sign up to set email alerts
|

A pivotal role for endogenous TGF-β-activated kinase-1 in the LKB1/AMP-activated protein kinase energy-sensor pathway

Abstract: TGF-␤-activated kinase-1 (TAK1), also known as MAPKK kinase-7 (MAP3K7), is a candidate effector of multiple circuits in cardiac biology and disease. Here, we show that inhibition of TAK1 in mice by a cardiac-specific dominant-negative mutation evokes electrophysiological and biochemical properties reminiscent of human Wolff-Parkinson-White syndrome, arising from mutations in AMPactivated protein kinase (AMPK), most notably, accelerated atrioventricular conduction and impaired AMPK activation. To test conclusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
244
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(259 citation statements)
references
References 49 publications
7
244
3
Order By: Relevance
“…14,15 Exogenous stressors and environmental changes such as osmotic stress, UV irradiation, ischemia and nutrient withdrawal activate TAK1. 13,14,16,17 Among these stimuli, the mechanism of TAK1 activation and its role in the TNFa signaling pathway has been extensively studied. Upon TNFa stimulation, adaptor molecules including TNFa receptor type-1-associated death domain protein (TRADD), TNFa receptorassociated factor 2 and 5 (TRAF2 and TRAF5), cellular inhibitor of apoptosis 1 and 2 (cIAP1/2) and RIPK1 are recruited to the receptor complex (TNF receptor 1 (TNFR1) Complex I) (Figure 1), in which RIPK1 acquires a K63-linked or linear polyubiquitin chain by E3 ligases, TRAF2/5 cIAP1/2 or linear ubiquitin chain assembly complex containing two E3 ligases HOIL-1 and HOIP.…”
Section: Tak1 Activation and Downstream Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Exogenous stressors and environmental changes such as osmotic stress, UV irradiation, ischemia and nutrient withdrawal activate TAK1. 13,14,16,17 Among these stimuli, the mechanism of TAK1 activation and its role in the TNFa signaling pathway has been extensively studied. Upon TNFa stimulation, adaptor molecules including TNFa receptor type-1-associated death domain protein (TRADD), TNFa receptorassociated factor 2 and 5 (TRAF2 and TRAF5), cellular inhibitor of apoptosis 1 and 2 (cIAP1/2) and RIPK1 are recruited to the receptor complex (TNF receptor 1 (TNFR1) Complex I) (Figure 1), in which RIPK1 acquires a K63-linked or linear polyubiquitin chain by E3 ligases, TRAF2/5 cIAP1/2 or linear ubiquitin chain assembly complex containing two E3 ligases HOIL-1 and HOIP.…”
Section: Tak1 Activation and Downstream Pathwaysmentioning
confidence: 99%
“…26,27 Drawing a link between TAK1 signaling and metabolism, studies have found that starvation and TRAIL induce autophagy in which TAK1 is actively involved by activating AMP-activated protein kinase and IKKs. 14,17,28,29 In summary, TAK1 responds to exogenous stress conditions through a variety of mechanisms including TNFa family Figure 1 TNFa induces cell survival, apoptosis and necroptosis. Upon TNFa stimulation, TNFR1 forms Complex I, in which RIPK1 acquires a polyubiquitin chain.…”
Section: Tak1 Activation and Downstream Pathwaysmentioning
confidence: 99%
“…AMPK activation was originally proposed to be dependent on Thr172 phosphorylation via action of upstream kinases including LKB1, 43,44 calmodulin-dependent protein kinase kinase II␤, 45 and Tak1. 46 However, Xie et al 47 suggested that LKB1 actually acts downstream of Tak1 in mouse fibroblasts. Because TGF-␤1 seems to be crucial in AMPK-dependent p38MAPK activation and because it is part of the FAK/Tak1/JNK pathway crucial for myofibroblast activation, 35 we chose to analyze Tak1 activation in aged fibroblasts treated with TGF-␤1 and AICAR.…”
Section: Rescue Of Defective Function Requires Ampk Activationmentioning
confidence: 99%
“…1 To date, three AMPKKs have been identified in the heart, the tumor suppressor kinase LKB1, a calmodulindependent protein kinase kinase, and a TGF-b-activated kinase-1. 26 Although LKB1 and TGF-b-activated kinase-1 are highly expressed in heart, calmodulin-dependent protein kinase kinase is expressed only at low levels. 27 To date, the role of either of these AMPKKs in the control of AMPK phosphorylation and activation has not been clearly defined.…”
Section: Ampk Activation During Ischemia/reperfusionmentioning
confidence: 99%
“…Recent evidence in endothelial cells suggests that PKC-z phosphorylates LKB1 at Ser428, resulting in an increased association of LKB1 with AMPK and consequent AMPK Thr172 phosphorylation by LKB1. 26 Whether a similar pathway exists in the heart has yet to be determined.…”
Section: Ampk Activation During Ischemia/reperfusionmentioning
confidence: 99%